Cooperative Control Mechanism of Efficient Driving and Support in Deep-Buried Thick Top-Coal Roadway: A Case Study - Chengjun Hu; Changliang Han; Lixin Wang; Baofu Zhao; Houqiang Yang (Energies, 2022)
For deep-buried thick top-coal roadways under high stress, there exists great difficulty in controlling the stability of the surrounding rock as well as in the necessity for low driving speeds. Taking the return air roadway 20201 (RAR 20201) of the Dahaize Coal Mine as the background, this paper presents a typical engineering case of a deep-buried thick top-coal roadway in a western mine. Through methods such as in situ investigation, theoretical analysis, numerical simulation and engineering practice, we studied the deformation and failure mechanisms of the surrounding rock in a deep-buried high-stress thick top-coal roadway, and revealed the driving speed effect. Results show that compared with shallow buried roadways, the deep-buried thick-roof coal roadway suffers a greater range of damage and failure. The roof damage is so deep that it exceeds the action range of bolts, resulting in the stress transferring to both sides, which affects the stability of the roadway surroundings. The curve of unloading disturbance stress produced by roadway head-on driving is in accordance with the “power exponential” composite function; that is, the faster the driving speed, the less unloading disturbance intensity that is exerted on the roof strata. This paper puts forward targeted cooperative control countermeasures of efficient driving and support in a deep-buried thick top-coal roadway. On one hand, the support efficiency of a single bolt is improved so as to reduce the overall support density; on the other hand, under low support density, the driving-supporting circulation efficiency is also accelerated so as to weaken the unloading disturbance and improve roadway formation speed. Engineering practice shows great control effect of the roadway surrounding rock, and the roadway formation speed is also greatly improved. This research can provide reference for efficient driving and support design in similar deep-buried thick top-coal roadways.